Distribution of polycyclic aromatic hydrocarbons (PAHs) found in water along the Northern Straits of Malacca - Wong, Richard C.S.; Liew, Meng Lai; Chan, Chun Foong (Malaysian Journal of Science, 2008)
Marine water samples were collected during the SESMA I expedition along the northern Straits of Malacca. The route encompassed the Klang islands, the estuaries of the Selangor, Bernam and Perak rivers, Pulau Sembilan, Pulau Jarak, the estuaries of the Dinding, Matang and Gula rivers, southern Penang and Pulau Perak. Samples were collected from the surface to 1.5-2.0 m depth from a total of 18 stations located along the straits. The samples were analyzed for concentrations of a range of persistent organic polycyclic aromatics hydrocarbons (PAHs) namely: naphthalene, fluorene, anthracene, fluoranthene and pyrene. The total of these five PAHs concentrations were found to vary between 0.58 to 79.26 ÂµgL-1. Sampel air laut telah diambil semasa ekspedisi SESMA I di sepanjang Selat Melaka. Laluan termasuklah pulau-pulau di Klang, kuala sungai Selangor, Sungai Bernam dan Sungai Perak, Pulau Sembilan, Pulau Jarak, kuala Sungai Dinding, Sungai Matang, Sungai Gula, selatan Pulau Pinang dan Pulau Perak. Kutipan sample dilakukan di bahagian permukaan air sehingga ke kedalaman 1.5 â€“ 2.0m di kesemua 18 stesyen di sepanjang selat. Analisis telah dijalankan ke atas sampel-sampel untuk mengetahui kepekatan hidrokarbon aromatic polisiklik (HAP), iaitu naftalena, florena, antrasena, fluorantena dan pirena. Jumlah kepekatan bagi kelima-lima PAH ini adalah di antara 0.58 ke 79.26 mgL-1.